Do Geese Facilitate or Compete with Wintering Hooded Cranes (Grus monacha) for Forage Resources? - Zhengrong Zhu; Lizhi Zhou; Chao Yu; Lei Cheng; Wenbin Xu; Yunwei Song (Diversity, 2020)
Foraging is the key behavior of waterbirds, which profoundly affects the survival of their population, and it is affected by interspecific interaction. At Shengjin Lake in China, owing to the reduced availability of suitable habitats for a large population of migratory waterbirds (especially wild geese) over winter, mixed species foraging inevitably occurs. This study aimed to investigate whether mixed-species foraging affects the foraging of hooded cranes (Grus monacha). Fields surveys were carried out at Shengjin Lake from November 2018 to March 2019. Mixed-species foraging was surveyed between the flocks of hooded cranes and three species of geese, greater white-fronted geese (Anser albifrons), lesser white-fronted geese (Anser erythropus) and bean geese (Anser fabalis). Instantaneous scanning and focal animal methods were used to collect behavioral samples of hooded cranes. The quadrat method was used to survey the food density in three habitats: meadows, mudflats, and paddy fields. The results showed that the foraging success rate of hooded cranes was not significantly correlated with food density and the relative flock size in the mixed-species foraging flock in meadows, but a significant negative correlation with the relative flock size in mudflats. However in paddy fields it was a significant positive correlation with the relative flock size. Foraging efforts of hooded cranes were negatively correlated with food density and positively correlated with the relative flock size in meadows. In mudflats, foraging efforts of hooded cranes had a significant positively correlation with the relative flock size, however, there was a significant negative correlation with the relative flock size in paddy fields. To sum up, larger numbers of geese mixed with hooded cranes has a favorable effect on the foraging of hooded cranes in meadows and mudflats, however, the reverse was observed in the paddy fields.